(untitled) (Journal of Research Updates in Polymer Science, 2024)
By reinforcing casuarina equisetifolia leaf, a flexible bio fibre, in different volume proportions of 4%, 8%, 12%, 16%, and 20% into the epoxy resin, a bio-based composite was produced utilizing the hand layup method. FT IR spectrum was used to verify the production of epoxy casuarina composite. The produced composites have undergone an extensive thermal investigation using Differential Thermal Analysis (DTA), Thermogravimetric Analysis (TGA), Derivative Thermogravimetric (DTG) study and Differential Scanning Calorimetry (DSC) analysis. It has been observed that increasing the percentage of casuarina fibre content enhances the thermal stability of epoxy resin. Horowitz- Metzger (HM), Broido and Coats-Redfern (CR) models were worked and the result revealed that the decomposition of casuarina epoxy composite followed one Dimensional Diffusion Model with coefficient of correlation value close to 1. The thermodynamic parameters including Activation energy (Ea), frequency factor (A), Gibbs free energy (ΔG), entropy (ΔS) and enthalpy (ΔH) of epoxy casuarina composites were found to increase with increase in fibre contents. This makes the composite more suitable for making high performance engineering material for various applications.